Epigenetic marks on the chromatin are associated with RNA splicing in human leukemia cells - Ramanouskaya, Tatsiana V.; Kviatko, Anastasiya V.; Grinev, Vasily V. (Experimental Biology and Biotechnology, 2019)
In this work we estimated associations between distribution patterns of several epigenetic marks and splicing events on the level of full genome and transcriptome in the cells of two leukemic cell lines containing two different reciprocal chromosome translocations. Significant difference in distribution of epigenetic marks was found, contributing to more opened or more closed chromatin in loci of donor vs acceptor and canonical vs alternative splice sites in expressing genes. Marks of the opened chromatin are significantly more often present in the genomic regions with alternative splicing events than in regions with canonical splicing, while for the mark of the histone 3 trimethylation at lysine 36, the opposite trend is observed. The obtained results reveal the presence of an additional, still very poorly studied layer in the regulation of alternative splicing in human cells.